Exploring the rules of related parameters in acupuncture for post-stroke dysphagia based on data mining - Wu, Minmin; Song, Wenjing; Wang, Xue; Tang, Qiang; Gao, Weibin; Zhu, Luwen (Frontiers in Neurology, 2024)
Background Post-stroke dysphagia (PSD) affects the efficacy and safety of swallowing, causing serious complications. Acupuncture is a promising and cost-effective treatment for PSD; however, as the number of randomized controlled trials increases, scientific analysis of the parameters and acupoint prescription is required. Therefore, this study aimed to explore the effects of acupuncture on parameters related to post-stroke dysphagia (PSD). Methods We searched the Cochrane Library, PubMed, Embase, Web of Science, China National Knowledge Infrastructure, Wanfang Database, Chinese Biomedical Literature, and Chongqing VIP Database for randomized controlled trials of acupuncture for PSD in the last 15 years and relevant parameters were analyzed using data mining techniques. Results In total, 3,205 records were identified, of which 3,507 patients with PSD were included in 39 studies. The comprehensive analysis demonstrated that the closest parameter combinations of acupuncture on PSD were 0.25 mm × 40 mm needle size, 30 min retention time, five treatments per week, and a 4-week total course of treatment. Additionally, the gallbladder and nontraditional meridians, crossing points, and head and neck sites are the most commonly used acupoint parameters. The core acupoints identified were GB20, RN23, EX-HN14, Gongxue, MS6, SJ17, EX-HN12, EX-HN13, and the commonly used combination of EX-HN12, EX-HN13, GB20, and RN23. Conclusion This study analyzed the patterns of PSD-related needling and acupoint parameters to provide evidence-based guidelines for clinical acupuncturists in treating PSD, potentially benefitting affected patients.